Young children’s at-home digital experiences and interactions: an ethnographic study - Lewis, K. L.; Kervin, L. K.; Verenikina, I.; Howard, S. J. (Frontiers in Education, 2024)
Introduction: Young children are increasingly provided with opportunities to interact with digital technologies in their homes. Despite an accumulating body of research on children's digital interactions, little is known about how these are situated within the social and cultural context in which they take place. In this exploratory study, we aim to extend existing knowledge by offering a contextualised understanding of children's digital experiences. To do this, we draw on Engeström's (1993) Activity Theory as a conceptual framework to explore how various social and cultural factors influence and interact to shape children's opportunities and interactions with digital technologies. Method: This study draws upon ethnographic and 'day in the life' methodologies to gain rich insight into children's situated digital experiences. Along with other traditional ethnographic methodologies, children aged between 3 and 6 years from 5 families were provided with wearable chest-mounted video cameras to capture their usual daily play activities at home -which included, but was not limited to, digital activities. Results: Data on digital interactions is presented for the five participating families, and through the presentation of two purposively selected in-depth illustrative examples, we demonstrate how children's digital interactions are part of a larger activity system situated within the social and cultural contexts of their homes. We also elaborate on children's natural inclination to interact playfully with digital technologies. Discussion: This study extends on current knowledges about the contextual influences of children's digital experiences and has important implications for parents and families trying to navigate the complexities of their children's digital lives.